Optimum conditions for growth in liquid medium of Oscillatoria formosa Bory used as the principal food in laboratory culture of intermediate hosts for schistosomosis and fasciolosis - Ferreira Filipa M.; Delgado M.L.; Seixas Lopes A.M.; Sampaio Silva M.L. (Parasite, 2000)
The rearing of snails, intermediate hosts of Schistosoma haematobium, S. intercalatum, S. bovis and Fasciola hepatica is the first step to maintain the life cycle of these parasites in laboratory in order to have biological material for the different studies, namely on the systematic biology and immunodiagnostic of schistosomosis and fasciolosis. According to the traditional method, the alga Oscillatoria formosa Bory (Cyanobacteria), principal food source for the snails, was cultivated in soil extract (Sampaio Xavier et al., 1968). However, it was sometimes very difficult to find the proper soil extract and the material was also contaminated by protozoa and fungi. In our work, using a new medium having as a base the Mineral Medium II (modified from Hughes et al., 1958) we found that O. formosa had a better growth response than in the soil extract medium. Snails fed on O. formosa reached three times the size of others at the same age, and they also reached sex maturity earlier, having more egg-masses per snail and, in addition, the rate of survival as well as the number of generations per year under laboratory conditions significantly increased. This culture was also easier to perform, and the axenic conditions easier to maintain.